2022
DOI: 10.1007/s10458-022-09573-7
|View full text |Cite
|
Sign up to set email alerts
|

Topological influence and locality in swap schelling games

Abstract: Residential segregation is a wide-spread phenomenon that can be observed in almost every major city. In these urban areas residents with different racial or socioeconomic background tend to form homogeneous clusters. Schelling’s famous agent-based model for residential segregation explains how such clusters can form even if all agents are tolerant, i.e., if they agree to live in mixed neighborhoods. For segregation to occur, all it needs is a slight bias towards agents preferring similar neighbors. Very recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Later, in eorem 5.11), we will show that the bound holds even in the presence of stubborn agents. We should note that a er the conference version of our paper, Bilò et al [2020] improved the bound to 3 for the fully-strategic case. eorem 5.8. e social price of anarchy of fully-strategic balanced 2-swap games with at least two agents per type and connected topology is between 667/324 ≈ 2.…”
Section: Swap Gamesmentioning
confidence: 80%
See 1 more Smart Citation
“…Later, in eorem 5.11), we will show that the bound holds even in the presence of stubborn agents. We should note that a er the conference version of our paper, Bilò et al [2020] improved the bound to 3 for the fully-strategic case. eorem 5.8. e social price of anarchy of fully-strategic balanced 2-swap games with at least two agents per type and connected topology is between 667/324 ≈ 2.…”
Section: Swap Gamesmentioning
confidence: 80%
“…A similar se ing with agents that derive linear utility both from their location as well as their nearby friends, was recently studied by Elkind et al [2020b]. Bilò et al [2020] examined the in uence of the topology and locality on the existence of equilibria and the price of anarchy in swap games. Chan et al [2020] introduced an alternative model wherein multiple agents can occupy the same location and, similarly to our social Schelling games (Section 7.1), there is a friendship network.…”
Section: Further Related Workmentioning
confidence: 99%
“…For this setting, the authors showed results similar to those of Elkind et al (2019). Bilò et al (2020) improved some of the price of anarchy bounds of Agarwal et al (2020), and also studied a variation of the model in which the agents have a restricted view of the topology and can only swap with their neighbors. Finally, Kanellopoulos, Kyropoulou, and Voudouris (2020) investigated the price of anarchy and stability in jump Schelling games, but with a slightly different utility function according to which an agent considers herself as part of her set of neighbors.…”
Section: Related Workmentioning
confidence: 84%
“…Most related to our present work are the papers (Elkind et al 2019;Agarwal et al 2020;Bilò et al 2020;Kanellopoulos, Kyropoulou, and Voudouris 2020), which studied game-theoretic and complexity questions related to the social welfare in Schelling games. In particular, Elkind et al ( 2019) considered jump Schelling games in which there are k ≥ 2 types of agents, and the topology is a graph with more nodes than agents so that there are empty nodes to which unhappy agents can jump.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation